THE IMPACT OF GENERATIVE AI ON LEARNING AND TEACHING PROCESSES: A CASE STUDY OF IMPLEMENTATION IN INDONESIAN HIGHER EDUCATION - Restian, Arina; Lin, Tun; Kaddour, Fatiha (Al-Hijr: Journal of Adulearn World, 2025)
Generative AI’s emergence presents a profound disruption to global higher education. Its rapid integration creates tensions between technological potential and established academic practices. This study investigates the impact of Generative AI on learning and teaching processes within the unique context of Indonesian higher education, exploring the complex interplay between this global technology and local institutional realities. The research objective was to analyze student adoption, faculty perceptions, and institutional responses to GenAI implementation. A qualitative case study methodology was employed, gathering data from students and faculty across several Indonesian universities. The findings reveal a significant misalignment: students exhibit rapid, pragmatic adoption, particularly for linguistic support, while faculty express deep ambivalence tied to academic integrity concerns and entrenched pedagogical cultures, such as the “guru” model. Institutional responses are largely reactive and fragmented, lacking cohesive policies or training. This study concludes that GenAI’s impact in Indonesia is not technologically deterministic but is profoundly mediated by local cultural-pedagogical norms and institutional inertia, resulting in a widening gap between student practice and formal education.